Psycholinguistic Dimensions of Intercultural Bonding in A Thousand Questions: A Lens from Vygotsky’s Sociocultural Theory - Halim, Nur Mutmainnna; Halim, Abd; Mappaita, Suci Pole (Journal of Language and Literature Studies, 2025)
This study explores the dynamics of language acquisition and emotional development within cross-cultural friendship, as portrayed in the novel A Thousand Questions by Saadia Faruqi. Anchored in the framework of Vygotsky’s Sociocultural Theory (1962) and approached through a qualitative lens, the research investigates how two main characters, Mimi and Sakina, engage in reciprocal language learning shaped by social interaction, cultural exchange, and emotional support. Using textual analysis as the primary method, this study identifies and interprets moments of scaffolding, mediation, and the Zone of Proximal Development (ZPD) within the characters' dialogue and interactions. The analysis reveals that code-switching, pragmatic negotiation, and context-sensitive lexical choices serve as psycholinguistic markers of evolving empathy, trust, and identity formation. These findings underscore that language development in intercultural youth contexts is driven not only by cognitive processes but also by affective-social mechanisms rooted in lived experience. By framing the novel as both a cultural artifact and a pedagogical resource, this study illuminates how fictional narratives can model principles of bilingual education, emotional literacy, and peer-mediated learning. The results have practical implications for educators and curriculum designers seeking to foster inclusive, culturally responsive language environments, especially in settings with diverse linguistic backgrounds.